Perkawinan Beda Agama dalam Paradigma Sosiological Jurisprudence - Roni Efendi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
The promulgation of the Marriage Law is as a tool of social engineering or an instrument to regulate the community and as a guideline for the community to carry out a marriage. So those friendships that are carried out are not based on or violate religious law contained in the Marriage Law deemed invalid, one of which is interfaith marriages. The diversity of Indonesian society has been regulated by several provisions and diverse institutions, moreover related to the requirements of marriage. The occurrence of social facts in the form of violation of the regulations of marriage in the way of interfaith marriages according to the Sociological jurisprudence school is the result of proper gradation, morals which have been the basis for the formation of law. If ethics or morals become evil, it will result in bad behavior, both the behavior of individuals, groups and state officials.